Struktur Kalimat Bahasa Indonesia Dan Bahasa Arab Dalam Karya Habiburrahman El Shirazy (Studi Analisis Kontrastif) - Nurul Fitriani; Rosidin, Odien; Kartika Devi, Ade Anggraini (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2023)
Each language has its characteristics, such as Indonesian and Arabic. Learning a language, especially a second language, must have difficulties. Contrastive analysis is a solution for language learners facing language learning difficulties. The problems are experienced in various forms, such as sentence structure. This study aims to analyze the sentence structure of Indonesian and Arabic in the work of Habiburrahman El Shirazy with the contraceptive analysis survey. The research method uses qualitative descriptive methods. The data analysis technique uses James' theory through the stages of description and comparison. Based on the research that has been carried out, the results are obtained, namely that there are similarities and differences in the structure of sentences in Indonesian and Arabic, which are then used as a solution to make it easier to learn a second language.